Electrophysiological and pathological changes in the vastus medialis and vastus lateralis muscles after early patellar reduction and nerve growth factor injection in rabbits with patellar dislocation - Yu Wu (Journal of Orthopaedic Surgery and Research, 2022)
Abstract Background Patellar dislocation can cause a series of changes in the trochlear groove and patella. However, the influence of patellar dislocation on the medialis (VM) and vastus lateralis (VL) muscles and whether nerve growth factor (NGF) is beneficial to proprioceptive rehabilitation for patellar dislocation are unknown. The purpose of this study was to investigate the effects on VM and VL after the injection of NGF and early reduction in rabbits for patellar dislocation with electrophysiological and pathological analysis. Methods Sixty 2-month-old rabbits were randomly divided into four groups (15 rabbits in each group). Rabbits in Group 1, Group 2, and Group 3 underwent patellar dislocation surgery, and rabbits in Group 4 underwent sham surgery. One month later, patellar reduction was performed in Groups 1 and 2. NGF was injected into the rabbits of Group 1. The electrophysiological and pathological changes in VM and VL were analyzed at 1 month and 3 months after patellar reduction. Results The electrophysiological and pathological indices in Groups 1 and 2 were significantly different from those in Group 3 at 1 and 3 months after patellar reduction. There were significant differences between NGF injection Group 1 and Group 2 without NGF injection. There was no significant difference between Group 1 and Group 4 at 3 months after patellar reduction. Conclusions Patellar dislocation can cause abnormal electrophysiological and pathological effects on VM and VL. Patellar reduction should be performed as early as possible, and NGF injection may be beneficial to the rehabilitation of proprioception.